1983
DOI: 10.1177/002221948301600807
|View full text |Cite
|
Sign up to set email alerts
|

Paraprofessionals in Learning Disabilities

Abstract: The purpose of this manuscript is to generate information about the paraprofessional concept as it relates to learning disabilities. A brief review of the paraprofessional literature is reported. The possible roles and responsibilities that could be included in a paraprofessional's job description were delineated and discussed. A structured, comprehensive, and flexible approach that LEA's could use to implement the concept was proposed. And the problems that are “inherent” in the paraprofessional concept were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For many years, paraprofessionals have been employed to provide assistance in special education programs, and special education teachers have held de facto responsibility for their supervision (Alexander, 1987;French & Pickett, 1997;Pickett, 1980Pickett, , 1986Pickett, , 1989Vasa, Steckelberg, & Ulrich-Ronning, 1982). There is some agreement that paraprofessionals perform their duties most effectively when they are appropriately supervised (Blalock, 1984;Boomer, 1980), when their roles are clearly defined (Blalock, 1991; Lindsey, 1983), when they are trained for assigned tasks (Courson & Heward, 1988;Frank, Keith, & Steil, 1988), and when they participate in regularly scheduled planning meetings (Miramontes, 1990;Pickett, Vasa, & Steckelberg, 1993).…”
Section: Supervising Paraprofessionalsmentioning
confidence: 99%
“…For many years, paraprofessionals have been employed to provide assistance in special education programs, and special education teachers have held de facto responsibility for their supervision (Alexander, 1987;French & Pickett, 1997;Pickett, 1980Pickett, , 1986Pickett, , 1989Vasa, Steckelberg, & Ulrich-Ronning, 1982). There is some agreement that paraprofessionals perform their duties most effectively when they are appropriately supervised (Blalock, 1984;Boomer, 1980), when their roles are clearly defined (Blalock, 1991; Lindsey, 1983), when they are trained for assigned tasks (Courson & Heward, 1988;Frank, Keith, & Steil, 1988), and when they participate in regularly scheduled planning meetings (Miramontes, 1990;Pickett, Vasa, & Steckelberg, 1993).…”
Section: Supervising Paraprofessionalsmentioning
confidence: 99%
“…It is possible that there are feedback pathways communicating error signals to the thalamus that are themselves optimized by evolution and confer corticothalamic synapses with the potential for error-driven plasticity. Modeling studies have shown that such an approach is effective in the context of feedforward networks (Lee, Zhang, Biard, & Bengio, 2014; Akrout, Wilson, Humphreys, Lillicrap, & Tweed, 2019; Lindsey & Litwin-Kumar, 2020), and would make for an interesting alternative hypothesis of learning in thalamocortical loops. However, the predictions of such a model would be difficult to test because to our knowledge, pathways conveying error signals to the thalamus, if any, are yet to be mapped out.…”
Section: Discussionmentioning
confidence: 99%